Lynch syndrome-associated colorectal cancer in a 16-year-old girl due to a de novo MSH2 mutation. Issue 7 (1st July 2020) - Zajo, Kristin; Colace, Susan I; Mouhlas, Danielle; Erdman, Steven H
Abstract : The diagnosis of paediatric colorectal cancer is an unusual finding often diagnosed at an advanced stage with associated poor survival. Paediatric colorectal cancer warrants investigation for hereditary cancer predisposition syndromes, including Lynch syndrome. Here we describe a 16-year-old girl who presented with a stage IIA mucinous adenocarcinoma of the descending colon (T3 N0 M0) treated by resection alone that was associated with a pathogenic germline mutation of MSH2 (c.1786_1788delAAT (p.Asn596del)). This previously described mutation was not found in either parent or her three siblings. To our knowledge, this is the earliest reported case of paediatric Lynch syndrome-associated colorectal cancer by de novo mutation of MSH2 . This case illustrates that although Lynch syndrome is typically described as an adult-onset cancer syndrome, Lynch syndrome-associated colorectal cancer can be found in children and adolescents. Genetic testing should be considered as a part of the initial evaluation in these patients.